2005
DOI: 10.1021/jp054954t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Platinum Content on the Microstructure and Micropore Size Distribution of Pt/Alumina-Pillared Clays

Abstract: The aim of this work is to study the effect of the platinum content (0-1.8 wt % Pt) on the microstructure of an alumina-pillared clay. For this purpose, the nitrogen physisorption data at -196 degrees C, the micropore size distributions of the supported platinum catalysts, and the hydrogen chemisorption results at 30 degrees C have been analyzed and compared. The preparation of the catalysts has modified the textural properties of the Al-pillared clay support, giving rise to a loss of surface area and micropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In addition, this result suggests that some Cu species may block the entrance to the porous network and/or occupy the inner pores of the Al-PILC during the preparation process and make it inaccessible. Similar events were reported by Barrega-Vargas et al (2005) and MarinkovicNeducin et al (2004).…”
Section: Characterizationsupporting
confidence: 90%
“…In addition, this result suggests that some Cu species may block the entrance to the porous network and/or occupy the inner pores of the Al-PILC during the preparation process and make it inaccessible. Similar events were reported by Barrega-Vargas et al (2005) and MarinkovicNeducin et al (2004).…”
Section: Characterizationsupporting
confidence: 90%
“…The authors indicated that if the amount of cations introduced in pillared clays can be effectively controlled, it is possible to fine-tube the properties of pillared clays. Recently, Barrera-Vargas et al (148) studied the effect of the platinum content (0 -1.8 wt.%) on the microstructure and micropore size distribution of Pt/Al-pillared clays. The authors reported that, from the results of characterization, the platinum species blocked the micropore entrances by steric hindrance to nitrogen access as the platinum content increased.…”
Section: Control Of the Microstructure Developed In Pillared Claysmentioning
confidence: 99%
“…The authors indicated as conclusion of the work that a sharpening of the micropore-size distribution and a shift to smaller pore diameters is expected as a consequence of the use of the modified Horvath-Kawazoe equations. These two approaches have been applied and compared by Gil et al (59,148,251) to characterize the microporosity of pillared interlayered clays, resulting in very similar micropore-size distributions (see Figure 7). …”
Section: The Horvath-kawazoe (Hk) Model For Slit-like Shaped Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahranowski et al (2000) studied the modification of the textural properties of Al-, Zr-, and Ti-pillared clays upon doping with copper, and showed that the effect of the copper addition on the texture of pillared solids depends on the nature of pillars and on the method of doping. The effect of the platinum content on the microstructure and the micropore size distribution of Pt/Al-pillared clays has been recently studied by Barrera-Vargas et al (2005). The authors reported that the platinum species block the micropore entrances by progressive steric hindrance to nitrogen access as the platinum content increases.…”
mentioning
confidence: 99%